2008
DOI: 10.1002/gepi.20323
|View full text |Cite
|
Sign up to set email alerts
|

Differential parental transmission of markers in RUNX2 among cleft case‐parent trios from four populations

Abstract: Isolated cleft lip with or without cleft palate (CL/P) is among the most common human birth defects, with a prevalence around 1 in 700 live births. The Runt-related transcription factor 2 (RUNX2) gene has been suggested as a candidate gene for CL/P based largely on mouse models; however, no human studies have focused on RUNX2 as a risk factor for CL/P. This study examines the association between markers in RUNX2 and isolated, nonsyndromic CL/P using a case-parent trio design, while considering parent-of-origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 38 publications
2
39
2
1
Order By: Relevance
“…It remains currently undetermined whether the TD in CEU fathers, which we observed in our study, has the potential to influence the outcome of the two above-mentioned studies. 15,16 If this holds true, one would expect that the excess of maternal transmission observed by Sull et al 16 might be even more pronounced than already found to lead to the 'disappearance' of the CEU paternal 'background TD' (the generally present TD, independent of phenotype) in the RUNX2 region. The absence of coding, non-synonymous polymorphisms among the markers found to be under TD points to the importance of regulatory regions (such as P1 and P2), 15,46 or to a role for the product of the MIRN586 gene.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It remains currently undetermined whether the TD in CEU fathers, which we observed in our study, has the potential to influence the outcome of the two above-mentioned studies. 15,16 If this holds true, one would expect that the excess of maternal transmission observed by Sull et al 16 might be even more pronounced than already found to lead to the 'disappearance' of the CEU paternal 'background TD' (the generally present TD, independent of phenotype) in the RUNX2 region. The absence of coding, non-synonymous polymorphisms among the markers found to be under TD points to the importance of regulatory regions (such as P1 and P2), 15,46 or to a role for the product of the MIRN586 gene.…”
Section: Discussionmentioning
confidence: 88%
“…Two association studies addressing the transmission of SNPs of RUNX2 within families have recently been published. The first 16 focused on affected trios from four populations, and found evidence of linkage of many SNPs in RUNX2 with cleft lip, but only when parent-of-origin effects were considered (which is indicative of genomic imprinting). We obtained evidence that most of these 11 SNPs can be subject to skewed transmission ratios as well, but only among YRI fathers (Supplementary File S3).…”
Section: Discussionmentioning
confidence: 99%
“…Considering cleft lip with or without cleft palate, the sex ratio is biased with more affected males than females and an excess of maternal transmission in sporadic cases has been reported for several disease-causing genes. [23][24][25][26] As cleft lip may harbor a social disadvantage and more males than females are affected, reduced fertility of affected individuals could lead to the observation of an excess of maternal transmission. Another example is hereditary cystatin C amyloid angiopathy (HCCAA), which is an autosomal dominant disease with high penetrance, responsible for brain hemorrhages in young normotensive adults.…”
Section: Discussionmentioning
confidence: 99%
“…This result most likely reflects the maternal genotype effect rather than imprinting, because several unrelated cases of maternal UPD6 have been described with no clinical impact, except for unmasking single gene disorders (Eggermann et al, 2001). However, a maternal genotype effect has been reported for isolated oral cleft and other disorders (Reutter et al, 2008;Sull et al, 2008Sull et al, , 2009). Our relative risk analyses revealed that both maternal and child genotypes for the 101-bp allele are in agreement, showing an increased cleft risk.…”
Section: Discussionmentioning
confidence: 99%